Mothers In Motion intervention effect on psychosocial health in young, low-income women with overweight or obesity - Chang, Mei-Wei; Nitzke, Susan; Brown, Roger (BMC public health, 2019)
Background Mothers in Motion (MIM), a community-based intervention program, was designed to help young, low-income women with overweight or obesity prevent further weight gain by promoting stress management, healthy eating, and physical activity. This paper presents the MIM’s intervention effect on self-efficacy to cope with stress, emotional coping response, social support for stress management, stress, depressive symptoms, and positive and negative affect. Methods Participants ( N = 612) were recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children in Michigan. They were randomly assigned to an intervention group (410 participants) or comparison group (202 participants). During the 16-week intervention, intervention participants watched ten video lessons at home and joined ten peer support group teleconferences. Surveys with established validity and reliability were used to measure self-efficacy to cope with stress, emotional coping response, and social support for stress management. The Perceived Stress Scale, Center for Epidemiologic Studies Depression Scale, and Positive and Negative Affect Scale were used to measure stress, depressive symptoms, and positive and negative affect, respectively. A general linear mixed model was applied to test the intervention effect at the end of the 16-week intervention (T2, n = 338) and at three-month follow-up (T3, n = 311). Results At T2, the intervention group reported significantly higher self-efficacy to cope with stress (effect size [Cohen’s d ] = 0.53), better emotional coping response ( d = 0.38), less stress ( d = 0.34), fewer depressive symptoms ( d = − 0.27), and more positive affect ( d = 0.31) than the comparison group. However, there were no significant differences in social support for stress management and negative affect between these two groups. At T3, the intervention group still reported significantly higher self-efficacy to cope with stress ( d = 0.32) and better emotional coping response ( d = 0.34) than the comparison group but did not report significantly higher social support for stress management, stress, depressive symptoms, and positive and negative affect. Conclusions To help young, low-income women with overweight or obesity manage stress, researchers and program planners may consider focusing on building self-efficacy to cope with stress. Trial registration Clinical Trials NCT01839708 ; registered February 28, 2013.